Bridging ancient wisdom and modern management: Enhancing I Ching learning with ChatGPT - Leung, Chi Hong; Chan, Winslet Ting Yan (Asian Journal of Contemporary Education, 2024)
This study aims to investigate the integration of artificial intelligence, specifically ChatGPT, into the learning process of the I Ching, and its impact on students’ understanding and application of this ancient Chinese wisdom in modern management practices. The research adopts a quantitative approach, utilizing surveys to collect data from students. ChatGPT, an artificial intelligence language model, is employed as a learning tool to assist students in applying the principles of the I Ching to solve business problems. The surveys evaluate students’ perceptions of ChatGPT’s usefulness, ease of use, and its effectiveness in practical applications of the I Ching. Additionally, the study examines ChatGPT’s responses to determine its knowledge of the I Ching. The findings affirm that ChatGPT possesses a fundamental understanding of the I Ching and can effectively apply it to solve problems presented in textbook cases. Students perceive ChatGPT as user-friendly and highly beneficial in learning how to apply the I Ching in practical scenarios. The integration of ChatGPT as a learning tool has not only enhanced accessibility to the I Ching but also elicited increased interest and engagement among students. This integration serves as a valuable bridge between ancient Chinese wisdom and modern management approaches. By harnessing the power of artificial intelligence, students can dynamically and interactively explore the depths of the I Ching, thereby enhancing their comprehension and application of its principles. Consequently, this integration not only facilitates the learning of the I Ching but also fosters greater interest and engagement among students in business school.